State-civil society alliance: Debates and challenges in co-management of educational inclusion policies in Uruguay and Argentina - Andres Peregalli (Arizona State University, 2020)
In Latin America different policies sustained in State-Civil Society alliances are implemented in order to warrant the right to education in marginalized sectors. Uruguay and Argentina carry out "bridge" programs and "completion" plans for adolescents, youngsters and adults to enter, re-enter or finish Medium Level Studies. I compare the characteristics of the alliance State-Civil Society in the co-management of the "Aulas Comunitarias" (Communitarian Classrooms) Program (PAC, Uruguay, 2007) and the "Plan de Finalización de Estudios Secundarios para Jóvenes y Adultos" (Finalization of Secondary Studies for youngsters and adults Plan) (FinEs 2, Argentina, 2008), aiming to understand their contributions to the processes of educational inclusion, as well as their limits. I analyze their genesis, political-institutional design/ways of organization and form of co-management contemplating: a) political-institutional approach to analyze public policy, b) Neo-institutionalism: sociopolitical as well as organizational and historic, c) co-management, d) educational management (paradigms: administrative and strategic). I implement a qualitative methodology, selecting co-management (as performed until December, 2015) as the unit of analysis. The findings show that PAC y FinEs 2 warrant the right to education supported by the attachment of several actors and sectors to their objectives. The quality of the contribution of alliances differs according the political-institutional design, kind of organization and forms of co-management: PAC shows a strategic co-management and FinEs 2 and administrative co-management.